Diagnostic Discrepancies in Small-volume Biopsy for the Initial Diagnosis, Recurrence, and Transformation of Follicular Lymphoma: A Multi-Institutional Collaborative Study. (20th December 2022) - Volaric, Ashley K.; Lin, Oscar; Balassanian, Ronald; Cook, Stephen; Falchi, Lorenzo; Fitzpatrick, Megan J.; Frank, Annabel K.; Gupta, Srishti; Hasserjian, Robert P.; Long, Steven; Ly, Amy; Menke, Joshua R.; et al.
Abstract : Small-volume biopsies (SVBs) including fine-needle aspiration (FNA), cell block, and needle core biopsies (NCB) are increasingly utilized to diagnose and guide the clinical management of lymphoma. We established a multi-institutional interdisciplinary collaboration of cytopathologists, hematopathologists, and oncologists focused on the role of SVB in the management of patients with follicular lymphoma (FL). To assess the performance characteristics of SVB in this setting, we evaluated all consecutive SVBs performed for clinical indications of initial diagnosis, recurrence, or transformation of FL over a 5-year period and focused on the 182 that had at least one subsequent biopsy within 3 months as part of the same clinical work-up. The most common outcome of a subsequent biopsy as part of the same clinical work-up was a more specific diagnosis usually assigning the pathologic grade (111/182, 61%), followed by a complete agreement with the SVB (24/182, 13%), and change from nondiagnostic on initial biopsy to diagnostic on subsequent biopsy (21/182, 12%). A minority resulted in a diagnostic change from benign to lymphoma (17/182, 9%), a change in FL grade (5/182, 3%), or change in the lymphoma diagnostic category (4/182, 2%). There were no cases where an initial diagnosis of lymphoma was overturned. The distribution of discrepancies was similar across initial SVB types (FNA, FNA + cell block, NCB with or without FNA). Tissue limitations were noted in a minority of cases (53/182, 29%) and were enriched among initially nondiagnostic biopsies (16/21, 76%). Flow cytometry immunophenotyping was performed in the majority of cases both at the first and last biopsy (147/182, 81%). SVB can be a powerful method to detect FL in various clinical indications, with discrepant cases mostly resulting from a refinement in the initial diagnosis.